Assessment of Intestinal Parasites, Enteric Bacterial Infections, and Antimicrobial Susceptibility among Street Food Handlers in Jimma Town, Southwest Ethiopia - Tibeso Gemechu; Teferi Eshetu; Tesfaye Kassa; Habtemu Jarso (Journal of Tropical Medicine, 2022)
Background. Food-borne infections are common public health problems worldwide. A street food handler with poor personal hygiene contributes to the transmission of intestinal parasites and enteric bacteria to the public via contaminated foods. In Ethiopia, health risks associated with street food are common. Previous studies in this area are scanty. Hence, the aim of this study was to determine the prevalence of intestinal parasites, enteric bacterial infections, and antimicrobial susceptibility among street food handlers in Jimma town. Methods. A cross-sectional study was conducted from October to December 2020 among 260 street food handlers in Jimma town. A semi-structured questionnaire was used to collect data through face-to-face interviews. About 3 grams of the fecal specimen were collected from each food handler for bacterial culture and concentration techniques. The data were entered into Epi-Data 3.1 and analyzed by SPSS version 20. Associated factors were identified by using binary logistic regression analysis. A statistically significant association was determined at a p-value less than 0.05. Results. The overall prevalence of intestinal parasites and enteric bacterial pathogens was 39.2% (33.3%–45.2%) and 8.85% (5.4%–12.3%), respectively. Ascaris lumbricoides (18.5%) and Salmonella (8.1%) were the most predominant parasite and enteric bacterial isolates, respectively. Not trimming fingernails (AOR = 2.884; 95% CI: 1.682–4.945) and not washing hands with soap after toilet (AOR = 3.342; 95% CI: 1.939–5.761) were factors associated with increased risk of infection by intestinal parasites or enteric bacterial pathogens. All Salmonella and Shigella isolates were 100% resistant to ampicillin. Conclusion. The infection with intestinal parasites and enteric bacterial pathogens detected in this study indicated that street food handlers may serve as sources of pathogens/parasites for transmission and experience morbidities due to the infections. Therefore, periodic medical checkups and creating awareness of personal hygiene are mandatory to reduce the risk of infections.